High‐performance high dynamic range image generation by inverted local patterns. Issue 12 (1st December 2015) - Hsia, Shih‐Chang; Kuo, Ting‐Tseng
Abstract : This study presents an image processing algorithm capable of generating high dynamic range (HDR) images from a single frame. On the basis of liquid crystal display (LCD) backlight theory, the proposed algorithm uses an inverted local pattern approach to adjust the histogram of lighting distribution. To improve processing efficiency, sampled images are classified into three types according to exposure characteristics, which are used to obtain suitable processing factor. The inverting factor is mixed with the original sample to darken the bright areas and brighten the dark areas in the images. Brightness enhancement and auto‐gain control are then added to expand the range of the grey levels. Authors' results demonstrate the efficacy of the proposed HDR algorithm in improving shadow details. In addition, single‐pass processing is used to reduce computational complexity, making the algorithm applicable for low‐power portable cameras and video recorders.